2014
DOI: 10.1002/2013ja019500
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of cosmic ray modulation in the solar minimum 23/24

Abstract: We study changes of the galactic cosmic ray (GCR) intensity for the ending period of the solar cycle 23 and the beginning of the solar cycle 24 using neutron monitors experimental data. We show that an increase of the GCR intensity in 2009 is generally related with decrease of the solar wind velocity U, the strength B of the interplanetary magnetic field (IMF), and the drift in negative (A < 0) polarity epoch. We present that temporal changes of rigidity dependence of the GCR intensity variation, before reachi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Mewaldt et al (2010) found ≈ 44 % growth of the parallel mean free path of GCR particles [λ ] from the minimum in 1997 to 2009 and its rapid reduction in 2010. Cliver, Richardson, and Ling (2013) stated that particle drifts were not the main processes in the recent minimum, but the GCR modulation was determined by diffusion and convection, contradicting the results obtained by Alania, Modzelewska, and Wawrzynczak (2014), i.e. that a drift related to the delay time between tilt angles of heliospheric current sheet and cosmic-ray intensity was an important reason for an increase of cosmic-ray intensity in 2009.…”
Section: Introductionmentioning
confidence: 89%
“…Mewaldt et al (2010) found ≈ 44 % growth of the parallel mean free path of GCR particles [λ ] from the minimum in 1997 to 2009 and its rapid reduction in 2010. Cliver, Richardson, and Ling (2013) stated that particle drifts were not the main processes in the recent minimum, but the GCR modulation was determined by diffusion and convection, contradicting the results obtained by Alania, Modzelewska, and Wawrzynczak (2014), i.e. that a drift related to the delay time between tilt angles of heliospheric current sheet and cosmic-ray intensity was an important reason for an increase of cosmic-ray intensity in 2009.…”
Section: Introductionmentioning
confidence: 89%
“…The UNLT theory was extended to allow for dynamical turbulence in [42]. If we consider particles moving much faster than the Alfvén speed, the static approximation should be accurate and equation (15) becomes in this case…”
Section: The Unlt Theorymentioning
confidence: 99%
“…The knowledge of the diffusion tensor is required in different physical scenarios such as modeling the propagation of cosmic particles in the Galaxy [10,11], studying solar modulation [12][13][14][15][16], and describing particles experiencing diffusive acceleration at interplanetary shocks [17][18][19][20][21] and interstellar shocks [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…At lower rigidities, drifts are present at all phases of a sunspot cycle [ Bieber et al, ; Asioka et al, ]. Potgieter et al ' s [] analysis of proton data from PAMELA spacecraft [ Adriani et al, ] confirmed Cliver et al's contention that residual modulation in 2009 is more diffusion like than in previous solar minima but insisting that drifts played a significant role although observed modulation effects are not well correlated with the waviness of the heliospheric current sheet (HCS) as in previous solar minima; also, see discussion by Alania et al [].…”
Section: Introductionmentioning
confidence: 99%